Peningkatan Keterampilan Penggunaan Whatsapp Business Sebagai Marketing Komunikasi Digital Dalam Meningkatkan Usaha Sentra Industri Tas Di Desa Truko, Kabupaten Kendal - Kharisma Ayu Febriana; Retno Manuhoro Setyowati; Yofiendi Indah Indainanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The era of digital marketing is the right solution for introducing products. Social media with its interactions has been widely used for promotion and interaction between business owners and potential buyers. The youth of this interaction provides a different experience between business owners and buyers which can increase the quality of trust and loyalty. The problem faced by this community is the inability to use the Whatsapp application through the Whatsapp business feature. If residents are successful in using this application, then business owners can promote their business, and target business opportunities in the digital realm. So that the output target to be achieved by the service team is how to teach WhatsApp business skills to members of the Kendal Bag Industry Center (SINTAK) in Truko Village, Kangkung District, Kendal Regency. The method used in this activity is a workshop. The results provide motivation and training on the use of WhatsApp business using experienced mentors in the field of digital communication so that they can help promote the Kendal Bag Industry (SINTAK) community product in Truko Village, Kangkung District, Kendal Regency.